Third molar position after class II subdivision malocclusion treatment with asymmetric extractions - Almeida, Jéssica Ferreira de (2019)
Introduction: This study aimed to assess the third molars angulation and their available space after Class II subdivision malocclusion treatment with asymmetric premolar extractions. Methods: The sample consisted of 37 patients in group 1 (Type 1 Class II subdivision) and 25 in group 2 (Type 2 Class II subdivision). In group 1 extractions were performed in the two maxillary quadrants and in the Class I mandibular quadrant. In group 2, extraction was performed in the Class II maxillary quadrant. Panoramic radiographs were used to evaluate third molars angulation and their available space. Radiographic measurements were performed with Dolphin® Imaging 11.9. T tests were used for intragroup comparison between the sides. Results: Generally, the results showed that both Groups demonstrated more favorable angulation and significantly greater space for third molars on the extraction quadrants. Both groups presented mesioangulation in mandibular third molars on the Class II side. Conclusions: Extraction therapy is associated with an improvement of space available and third molars angulation on the extraction quadrants.